Pengaruh Profitability dan Leverage terhadap Nilai Perusahaan - Saiful Bahgia; Azlina (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2022)
The purpose of this study is to examine the effect of profitability and leverage, either partially or jointly, on firm value in the construction of companies listed on the Indonesia Stock Exchange in 2017-2021. The data analysis method in this study uses multiple linear regression to predict the effect of the independent variables. The population in this study was the construction of the Indonesia Stock Exchange company building in 2017-2021, then 11 samples were obtained with 5 years of observation and 55 observations were obtained according to the criteria. The results showed that profitability and leverage, both simultaneously and partially, affected the value of the company's building construction companies listed on the Indonesia Stock Exchange for that period. Profitability affects the value of the company, this shows that high profits will lead to an increase in business value. Leverage does not affect firm value, this shows that a high level of leverage does not affect the number of short-term and long-term debts that must be paid off by the company.